El control interno contable de la cuenta gastos no deducibles y su aporte a la razonabilidad de los estados financieros - Guanuche Peñafiel, Dario Rodrigo (2015)
Over the years the internal control has played a leading role in resource management of a company especially account non-deductible expenses, ranch Two new Santa Cruz presented drawbacks in this area, which is why this work He started in order to give answer to the question: How influences costs nondeductible expenses to the reasonableness of the financial statements the accounting internal control? Objective and that is the main guideline of this project. We worked with exploratory research as a methodology for surveys of information, using instruments such as observation and interview allowed validation of the issue at hand which is the mismanagement of the costs has not deductible by the directors of the company, Data collection was set as the stage at which the direct application of the medium being used as a tool to obtain valid statistical data to support or strengthen an inquiry is made. As a result we have the area of accounting documents is not supported by most of the bills, there are many personal expenses of the business owner, to do the accountant said the company has not conducted an internal control periodically to account nondeductible expenses. It was concluded that the Hacienda. Two new Santa Cruz really has no policies and procedures for proper recording of transactions with regard to operational expenses. Finally the company is recommended to develop policies to establish an appropriate scheme of recording transactions in what you have to do to operating expenses and evaluate the impact of non-deductible expenses in paying taxes.